PENGARUH KEPEMIMPINAN,KOMPENSASI DAN DUKUNGAN REKAN KERJA TERHADAP KEPUASAN KERJA GURU DI SMKN 4 KOTA SUNGAI PENUH - Deky Hamdani (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to examine and analyze the effect of leadership, compensation, and peer support on teacher job satisfaction at SMKN 4 Kota Sungai Penuh. The results of data analysis show that: Partially the influence of Leadership, Compensation and Support of colleagues, namely: There is a negative influence and there is no significant influence between Leadership on Teacher Job Satisfaction at SMKN 4 Sungai Penuh City, this is evidenced by t count < t table (0.628 < 2.03693) and sig > (0.535 > 0.05) then Ho is accepted and Ha is rejected. There is a positive and significant influence between Compensation on Teacher Job Satisfaction at SMKN 4 Kota Sungai Penuh, this is evidenced by t count > t table (2.266 > 2.03693) and sig < (0.030 < 0.05), then H0 is rejected and Ha is accepted. There is a negative influence and there is no significant effect between Coworker Support on Teacher Job Satisfaction at SMKN 4 Sungai Penuh City, this is evidenced by t count < t table (0.494 < 2.03693) and sig > (0.625> 0.05) then Ho is accepted and Ha is rejected. The influence of Leadership, Compensation and Support of Teacher Colleagues on Teacher Job Satisfaction at SMKN 4 Kota Sungai Penuh is 44.8% while the remaining 55.2% is explained by other causal factors not examined in this study